Microneedling: is it still a good treatment for acne scars? A literature review (2020-2024) - Cardoso de Oliveira, Sofia; Ramalho Pinheiro, Sara; Costa e Silva, Salomé (Aesthetic Medicine, 2025)
Background: Acne is a highly prevalent condition that leads to both psychological distress and physical consequences, such as scarring. Several techniques have been used to treat acne scars, with microneedling (MN) being one of the most prominent methods. MN has been extensively studied for its efficacy and safety. Aims: To compare MN with other techniques for the treatment of acne scars. Methods: A literature review was conducted on PubMed using the terms “microneedling,” “micro-needling,” “percutaneous collagen induction,” “cicatrix,” “acne vulgaris,” “acne,” and “scar,” focusing on articles published between 2020 and 2024. Relevant studies were selected after screening their title, abstract and full text. Results: Fifteen articles were selected, all of which assessed the efficacy and safety of MN in treating acne scars compared to other treatment modalities. The results consistently demonstrated that MN alone and combined with other techniques is a safe and effective option for improving acne scars. Conclusion: In this literature review, several techniques were shown to be effective in improving acne scars, including MN, chemical peels, laser therapy, radiofrequency, and platelet-rich plasma. MN is particularly noted for its safety in individuals with darker skin types, and is well-tolerated and effective for the treatment of acne scars. The studies suggest that combining multiple techniques to enhance skin texture yields better results than a monotherapy treatment.